Maternal-Fetal Conflict During Infection: Lessons From a Mouse Model of Placental Malaria - Pandya, Yash; Penha-Gonçalves, Carlos (Frontiers in Microbiology, 2019)
Infections that reach the placenta via maternal blood can target the fetal-placental barrier and are associated with reduced birth weight, increased stillbirth, miscarriage and perinatal mortality. Malaria during pregnancy can lead to infection of the placental tissue and to adverse effects on the unborn child even if the parasite is successfully cleared, indicating that placental sufficiency is significantly compromised. Human samples and animal models of placental malaria have been used to unravel mechanisms contributing to this insufficiency and have implicated molecular pathways related to inflammation, innate immunity and nutrient transport. Remarkably, fetal TLR4 was found to take part in placental responses that protect the fetus, in contrast to maternal TLR4 responses that presumably preserve the mother‘s health but result in reduced fetal viability. We propose that this conflict of fetal and maternal responses is a determinant of the clinical outcomes of placental malaria and that fetally derived trophoblasts are on the front lines of this conflict.